Collecting qualitative data a practical guide to textual, media and virtual techniques - Braun, Virginia; Clarke, Victoria; Gray, Debra (Cambridge, UK Cambridge University Press, 2017)
Is there more to qualitative data collection than face-to-face interviews? Answering with a resounding 'yes', this book introduces the reader to a wide array of exciting and novel techniques for collecting qualitative data in the social and health sciences. Collecting Qualitative Data offers a practical and accessible guide to textual, media and virtual methods currently under-utilised within qualitative research. Contributors from a range of disciplines share their experiences of implementing a particular technique, provide step-by-step guidance to using that approach, and highlight both the potential and pitfalls. From gathering blog data to the story completion method to conducting focus groups online, the methods and data types featured in this book are ideally suited to student projects and other time- and resource-limited research. In presenting several innovative ways that data can be collected, new modes of scholarship and new research orientations are opened up to student researchers and established scholars alike.--Publisher's website.
Keywords: Qualitative research -- Methodology; Social sciences -- Research -- Methodology